Validation of a cephalometric prediction model for third molar eruption - Mercedes Rodríguez del Toro; Liuba González Espangler; Lázaro Ibrahim Romero García; Luis Atilano Soto Cantero (Editorial Ciencias Médicas, 2021)
Introduction: Early intervention in the abnormal eruption of third molars could reduce the number of patients with associated discomfort and the appearance of alterations caused by dental retention. Objective: Validate the cephalometric prediction model for third molar eruption developed by González Espangler. Methods: A cross-sectional longitudinal descriptive study was conducted of adolescents from Rafael María de Mendive Senior High School in Santiago de Cuba from January 2017 to March 2020. The two random samples examined consisted of 21 students aged 15-18 years and 29 health sciences professionals. The variables considered were sex, skin color, location, training stage, posterior bony space, angulation, mesiodistal diameter, predictive factors and type of third molar eruption. Results: Abnormal eruption prevailed: 19.0% in location 1.8; 17.9% in 2.8; 21.4% in 3.8 and 20.2% in 4.8. Significant differences were not observed between average values for posterior bony space, angulation and mesiodistal diameter, and the study reference. Validation of the model by expert criteria obtained a global agreement score of 100%. Conclusions: The cephalometric prediction model validated in the study is viable for the prediction of third molar eruptions in the population.